Facil authentication as an extra support in virtual learning environments to avoid academic fraud - Francisco David Guillén Gámez; Javier Bravo Agapito (Centro de Estudios Financieros, 2016)
Currently, both teachers and students are adapting themselves to the new technologies offered by the XXI century. In the case of teachers, this adaptation is greater since there is a need to adapt learning to new technologies, lifestyles and habits. One of the possibilities that information and communication technologies (ICT) offer us is to provide learning management systems, with flexible learning, that allows us to manage and evaluate different activities of an e-learning process. Despite the progress made in the field of e-learning, there is a very low number of works that allow through proper mechanisms to a correct identification of students when they do their on-line activities to prevent cheating. Although current learning management systems include tools for user authentication, they only verify the user's identity at the time of login through a username and password, but it does not certify that it is the correct student. Against this trouble, the use of facial authentication software in on-line activities which students have to do, allows us to identify and prevent those students who might cheat. This research project seeks to propose a mechanism or technique to ensure the correct access to the student within a learning platform, that is to say, the student is the one who really is, through a facial recognition software called Smowl.